The Effectiveness of the Application of Digital Technology and Learning Videos in the Process of Writing Inspirational Stories - Bawamenewi, Arozatulo; Giawa, Prilian Putri Cahyani; Tafonao, Sesilia Putri Kurnia Wati; Gulo, Necis Putra (Journal International of Lingua and Technology, 2024)
This study aims to determine the effectiveness of digital technology and learning videos in the process of writing inspirational stories. The research was conducted with the experimental method of pre-experimental design (nondesign), namely one group pretest-posttest design (one class only) with the research subject of class IX-A students of SMP Negeri 1 Idanogawo totaling 32 people. The results showed that the percentage of effectiveness of digital technology and learning videos was 80.5% with a decent category and an average score of 76.5. The benefits of digital technology and learning videos include: (1) the emergence of innovative learning methods/strategies, (2) encouraging teachers to be more creative, (3) making it easier to access learning resources, (4) making it easier for teachers to deliver material, (5) making it easier for students to understand the topics discussed, (6) saving time.